KUALITAS PRODUK DAN PELAYANAN TERHADAP KEPUTUSAN PEMBELIAN PADA PERUSAHAAN DAGANG RABINDO TAMA - Riaz Muhammad Khatami; Listiawati Listiawati; Kenedi Kenedi (Indonesian Journal of Thousand Literacies, 2023)
he quality of products and services in the field of trading business is very influential on sales. One of the businesses engaged in the trading business is the Rapinda Tama Trade Company. Based on sales data, it was found that there was a decrease in sales for several items which caused a decrease in sales. This study aims to determine the effect of product quality and service quality on purchasing decisions at Rabindo Tama Trading Company. This method uses a quantitative approach with saturated sampling techniques, the number of samples used is 100 respondents. Then analyzed using multiple linear regression analysis, the coefficient of determination, t test and F test. The results of the research variable product quality and service quality have a partially significant influence on purchasing decisions by showing the value of product quality variables on purchases of 0.000 <0.05 and quality service to the buyer's decision of 0.000 <0.05. Simultaneously the quality of products and services influences purchasing decisions, as evidenced by F count > F table, or 36.781 > 3.09. Simultaneously the quality of products and services affects purchasing decisions